2020
DOI: 10.1088/1361-6528/ab7043
|View full text |Cite
|
Sign up to set email alerts
|

Well-ordered nanoparticle arrays for floating gate memory applications

Abstract: A non-volatile floating gate memory device containing well-ordered Au nanoparticles (NPs) is fabricated as a metal–oxide–semiconductor capacitor structure. With superior control on the size, shape and position of nanoparticles, the presented nano-floating gate memory (NFGM) device possesses almost perfect precision of device geometry. The well-ordered Au NPs embedded within the memory device exhibit large memory window at low operation voltages (8.8V @ ± 15V), fast operation time (<10−4 s) and good retention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…These C-V trends and the bi-directional hysteresis under reverse bias can also be attributed to the existence of the deep-level states and interface states [47][48][49]. In light of these results, it can be concluded that -1.25 V < Vb < -2.1V reverse voltage range is the optimum voltage range for the operation of the photodiode with high responsivity.…”
Section: Resultsmentioning
confidence: 74%
“…These C-V trends and the bi-directional hysteresis under reverse bias can also be attributed to the existence of the deep-level states and interface states [47][48][49]. In light of these results, it can be concluded that -1.25 V < Vb < -2.1V reverse voltage range is the optimum voltage range for the operation of the photodiode with high responsivity.…”
Section: Resultsmentioning
confidence: 74%
“…3 , while during the 100-cycle endurance test, the stable current ratio of more than 5×10 2 is obtained. The retention property is analyzed, where the fast electrons detrapping degrades the retention time.…”
mentioning
confidence: 91%
“…However, there may be heterojunction effect, where the Fermi levels alignment causes the band bending and the built-in field that hinders or facilitates the injection of the carriers from the active layer to the charge trapping layer. The band bending and the built-in field caused by the energy level alignment has also been proved in organic heterojunctions, such as in Copper (II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31Hphthalocyanine (F 16 CuPc)/ Copper (II) Phthalocyanine (CuPc) heterojunction [20], in Zinc Phthalocyanine (ZnPc)/ fullerene (C 60 ) heterojunction [21]. The band bending due to the Fermi-level alignment causes space charge regions that the charge accumulates at the heterojunction interface to form accumulation-type heterojunction, or charge depletes at the heterojunction interface to form depletion-type heterojunction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, NVM devices based on metallic nanoparticles as a floating gate have gained more advantages, such as higher tapping probability of charges, ensuring the stable probability of retention property in case of defects in the tunneling or control oxide layer, and larger memory window [ 8 , 32 , 33 , 34 ]. In this context, metal nanoparticles as floating gate layer in NVM devices offer a noteworthy consideration in the memory operations subjected to attain high programming or erasing properties, a greater probability of the charge retention, and preferable density of state (DOS) near the fermi-level [ 32 , 33 , 35 , 36 , 37 , 38 ]. Additionally, metal oxide semiconductor field-effect transistor (FET)-related NVM devices are also investigated for memory operations such as read-only memory, endurance, and retention [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%